Postmortem Heart Weights and Valvular Circumference of Apparently Healthy Adult Nigerian Decedents - an Observational Study (2022)
Introduction: Organ weights at postmortem examination of deceased Nigerians are compared with those of Caucasians to determine pathologies and cause of death. Indigenous data are needed because of differences in race and lifestyle. Materials and Methods: This was an eleven-year retrospective study. Postmortem findings and summarized clinical notes of deceased Nigerians archived in the Department of Pathology, University College Hospital, Ibadan, from January 1, 2008 to December 31, 2018 were reviewed. Inclusion criteria were age 18–70 years, traumatic or sudden unexpected death with no pathology in the heart, and no history or postmortem features of hypertension. Data on age, gender, cause of death, body length, heart weights, heart valve circumferences, and ventricular wall thickness were retrieved. Descriptive statistics, Student’s t-test, and regression analysis were performed using SPSS version 20. Confidence limits were set at p < 0.05. Results: Eighty-five cases fulfilled the criteria, comprising 64 males and 21 females, with mean ages of 39.1 ± 13.8 years and 37.2 ± 11.0 years, respectively. The mean heart weights for males and females differed significantly, with means of 310.8 ± 40.3 g (220–405 g) and 261.3 ± 34.0 g (200–325 g), respectively (p < 0.0001). The mean body lengths also differed significantly, with males at 1.70 ± 0.1 m and females at 1.62 ± 0.1 m (p < 0.002). There was no significant difference in age between males and females (p > 0.05). Multiple regression analysis suggested that only gender was a likely predictor of heart weight (p < 0.001). The mean circumferences of the tricuspid, mitral, pulmonary, and aortic valves were 11.2 cm, 9.3 cm, 7.2 cm, and 6.4 cm, respectively, while the mean left and right ventricular wall thicknesses were 1.3 cm and 0.3 cm, respectively. Conclusion: Heart weights and valvular circumferences of apparently healthy adult Nigerians differ by gender and show ranges beyond values reported in other populations. These findings highlight the need for locally derived nomograms for postmortem assessments.